Helicobacter pylori reinfection with identical organisms: transmission by the patients' spouses. Issue 6 (June 1995) - Schütze, K; Hentschel, E; Dragosics, B; Hirschl, A M
Abstract : Reinfection with Helicobacter pylori after eradication is responsible for the recurrence of duodenal ulcer disease. The mode of transmission has not yet been established. In this study, 18 patients with chronic duodenal ulcers in whom H pylori had been eradicated with amoxicillin and metronidazole were entered into a prospective follow up study. Control endoscopies were performed 4, 8, 14, 27, and 43 months after starting treatment and the results of direct tests were compared with the kinetics of H pylori specific IgG titres. After eradication there was a noticeable and consistent fall in anti-H pylori IgG, while reinfections were characterised by a significant increase in specific titres. Reinfection was detected in two patients after 14 and 43 months, respectively. The H pylori strains responsible for these reinfections, the corresponding pretreatment isolates, and the strains isolated from the spouses of these patients were examined by polymerase chain reaction based DNA fingerprinting. Analysis showed that reinfection had been caused by the same H pylori strain and identified the spouses of these patients as carriers of the identical strain. Considering the genomic diversity and the interpatient heterogeneity of H pylori these results suggest a person to person transmission of H pylori reinfection. By the end of the observation period reflux oesophagitis had developed in 10 of the 16 patients who had not been reinfected. This surprising finding may be explained by the changed eating habits of patients after healing of duodenal ulcer disease.